2019
DOI: 10.1108/cdi-07-2018-0191
|View full text |Cite
|
Sign up to set email alerts
|

The careers of university professional staff: a systematic literature review

Abstract: Purpose Human capital is a key component of the success of organisations, and career development of staff is a vital component to both increasing and retaining human capital. Universities are no different, their people are key to their mission. There has been limited rigorous study of the careers of professional staff in the academy. The paper aims to discuss these issues. Design/methodology/approach A systematic literature review methodology resulted in a review of 23 articles dedicated to research on caree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 68 publications
0
21
1
Order By: Relevance
“…It has been argued here that a form of contemporary career, the hybrid career with its various subjective and objective boundaries, may be useful in understanding employee expectations of organisations in the 21st century. Individuals have been shown to welcome a more reciprocal relationship between themselves and the organisation in terms of career management (Gander et al, 2019). By understanding staff working in organisations and their career requirements, employers can respond accordingly to meld the organisations' and employees' needs in a contemporary career manner and to move towards a more compassionate organisational relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued here that a form of contemporary career, the hybrid career with its various subjective and objective boundaries, may be useful in understanding employee expectations of organisations in the 21st century. Individuals have been shown to welcome a more reciprocal relationship between themselves and the organisation in terms of career management (Gander et al, 2019). By understanding staff working in organisations and their career requirements, employers can respond accordingly to meld the organisations' and employees' needs in a contemporary career manner and to move towards a more compassionate organisational relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Gander (2018) found that CDI 26,7 university professional staff created hybrid careers, valuing job security, a career and promotion opportunities (traditional career concept), training for the external job market (boundaryless career concept) and meaningful work and autonomy (protean career concept). Table 1 outlines the different aspects of the traditional, protean, boundaryless and hybrid career (Gander, 2019;Clarke, 2013;Bridgstock, 2005).…”
Section: The Hybrid Career Concept 853mentioning
confidence: 99%
See 1 more Smart Citation
“…The careers of these new cadre of university professional staff, as discussed above, have not been significantly studied (Gander et al , 2019). This is especially true of the area of professional development (Coomber, 2019), even though professional associations for university professional staff are common (for example, Association of University Administrators in the UK, Association for Tertiary Education Management in Australia and Canacian Association of University Business Officers in Canada).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the digital age, the importance of intellectual capital and knowledge management to survive in the face of growing competition has increased. Therefore, in recent years, the central object of many modern studies has become personnel as the carrier of the company's human capital (Gander et al, 2019). Another important component of the management system is knowledge management, which makes it possible to systematize and integrate knowledge and disseminate it in all departments of the organization.…”
Section: Literature Reviewmentioning
confidence: 99%